The international tribunal for the law of the sea and the significance of urgent proceedings - Hamid, Abdul Ghafur@Khin Maung Sein (IIUM Press, 2011)
The International Tribunal for the Law of the Sea (ITLOS) is entrusted by the UNCLOS 1982 with the authority to settle disputes concerning the law of the sea. Although these disputes may be brought to other international courts and tribunals, ITLOS has a core competence to deal with all disputes submitted to it under the Convention. As an international judicial body with specialized jurisdiction, it plays a major role in the settlement of law of the sea disputes. This role is enhanced by the fact that the Convention confers on the Tribunal certain functions which are indeed unique in international adjudication. The present chapter mainly focuses on this unique jurisdiction of the Tribunal, known as urgent proceedings, which include provisional measures and prompt release of vessels and crew.